Molecular dynamics of nanostructures and nanoionics simulations in complex systems - Habasaki, Junko, 1955- (Singapore : Jenny Stanford Publishing, 2021)
Nanostructured materials with multiple components and complex structures are the current focus of research and are expected to develop further for material designs in many applications in electrochemical, colloidal, medical, pharmaceutical, and several other fields. This book discusses complex nanostructured systems exemplified by nanoporous silicates, spontaneously formed gels from silica-nanocolloidal solutions, and related systems, and examines them using molecular dynamics simulations. Nanoporous materials, nanocolloidal systems, and gels are useful in many applications and can be used in electric devices and storage, and for gas, ion, and drug delivery. The book gives an overview of the history, current status, and frontiers of the field. It also discusses the fundamental aspects related to the common behaviors of some of these systems and common analytical methods to treat them.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructures; Molecular dynamics; Nanostructured materials; MEDICAL / Biotechnology; SCIENCE / Nanostructures; SCIENCE / Life Sciences / General